EVALUATION OF VECTOR COMPETENCE OF ADULT IXODID TICKS FOR Anaplasma marginale, Babesia bigemina and Theileria annulataIN CATTLE FROM CENTRAL PUNJAB, PAKISTAN - Farhan Ahmad Atif; Kashif Hussain; Taleeha Roheen; Muhammad Haider Jabbar; Ammar Tahir (Journal of Animal and Plant Sciences, 2025)
Anaplasmosis, theileriosis and babesiosis, are the most important tick-borne diseases (TBDs), causing great financial losses to the livestock industry. The objective of the study was to evaluate the biological transmission dynamics of tick-borne diseases in cattle using conventional (blood smear), serological (cELISA), and cutting-edge modern techniques (PCR). For the biological transmission study, pathogen-free ticks were collected and divided into three groups. Each group of ticks was allowed for acquisition feeding for seven days on the respective diseased calves (anaplasmosis, theileriosis, and babesiosis), separately. Later, the infected ticks were allowed to feed on disease-free calves (n=15) and divided into three groups, comprising five calves in each group. After two weeks, calves were screened by serological and/or molecular assays. All five calves infested with Rhipicephalus microplus ticks transmitted (100%) Anaplasma marginale and Babesia bigemina infections. Whereas, calves infested with Hyalomma anatolicumanatolicum ticks transmitted (80%) Theileria annulata infection in four out of five calves. Hence, it was proved that R. microplus (A. marginale, B. bigemina) and H.anatolicumanatolicum (T. annulata) ticks are competent vectors in the region. The identification of vectors and determinants can help in the control and prevention of TBDs.
Keywords: Biological; transmission; tick-borne diseases; cattle